Analisis Perubahan Makna Kata dalam Novel Sisi Tergelap Surga Karya Brian Khrisna - Zahra, Salsa Pramudita Az; Suroso, Eko (Ruang Kata, 2025)
The purpose of this study is to describe the changes in word meaning contained in the novel Sisi Tergelap Surga by Brian Khrisna. In this study, researchers used a qualitative approach combined with descriptive methods. The data used in this research is in the form of words that experience changes in meaning in the novel and the data source in this research is from the novel Sisi Tergelap SuRga by Brian Khrisna. The researcher applied reading and note-taking techniques to collect research data. The novel is read repeatedly to obtain data and record words that experience changes in meaning which are then analyzed according to the Big Indonesian Dictionary (KBBI), and instruments. The results showed that there were 25 words that experienced changes in meaning. The changes in meaning found include changes in the meaning of expansion (generalization) as many as 12 words, changes in the meaning of narrowing (specialization) as many as 5 words, changes in the meaning of exaltation (amelioration) as many as 2 words, changes in the meaning of decline (peyoration) as many as 1 word, changes in the meaning of the exchange of responses (synthesia) as many as 3 words and changes in the meaning of equality of nature (association) as many as 2 words